Laboratory-acquired scrub typhus and murine typhus infections: The argument for risk-based approach to biosafety requirements for Orientia tsutsugamushi and Rickettsia typhi laboratory activities - Blacksell, S; Robinson, M; Newton, P; Day, N (Oxford University Press, 2018)
This study examined the literature on laboratory-acquired infections (LAIs) associated with scrub typhus (Orientia tsutsugamushi) and murine typhus (Rickettsia typhi) research to provide an evidence base for biosafety and biocontainment. Scrub typhus LAIs were documented in 25 individuals, from 1931-2000 with 8 (32%) deaths during the pre-antibiotic era. There were 35 murine typhus LAI reports and no deaths. Results indicated that highest risk activities were working with infectious laboratory animals involving significant aerosol exposures, accidental self-inoculation or bite related infections. A risk-based biosafety approach for in vitro and in vivo culture of O. tsutsugamushi and R. typhi would require only high-risk activities (animal work or large culture volumes) be performed in high containment BSL3 laboratories. We argue that relatively low risk activities including inoculation of cell cultures or the early stages of in vitro growth using low volumes/low concentrations of infectious materials can be performed safely in BSL2 laboratories within a biological safety cabinet.